2019
DOI: 10.1002/chem.201900373
|View full text |Cite
|
Sign up to set email alerts
|

1,3,9‐Triaza‐2‐oxophenoxazine: An Artificial Nucleobase Forming Highly Stable Self‐Base Pairs with Three AgI Ions in a Duplex

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 87 publications
0
31
0
4
Order By: Relevance
“…Very recently, the T m values of duplexes containing fully matched and mismatched base pairs consisting of cytosine with each of the four natural bases in the presence or in the absence of Ag I ions were reported, but no detailed explanations on this matter were provided . The study indicated that the Δ T m values of duplexes containing a C‐C, a C‐A or a C‐T mismatch on addition of Ag I ions are +12, +9, and +3 to +6 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the T m values of duplexes containing fully matched and mismatched base pairs consisting of cytosine with each of the four natural bases in the presence or in the absence of Ag I ions were reported, but no detailed explanations on this matter were provided . The study indicated that the Δ T m values of duplexes containing a C‐C, a C‐A or a C‐T mismatch on addition of Ag I ions are +12, +9, and +3 to +6 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that 9‐TAP showed fluorescence at 440 nm with excitation at 365 nm at pH 7.0 . The fluorescence quantum yields of the P and N nucleosides were 0.17 and 0.28, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…TFOs (15‐mers) containing phenoxazine ( P ) and 9‐TAP ( N ) components were successfully synthesized according to our previous report (Figures S1 and S2 in the Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations